Outpatient physiotherapy versus home-based rehabilitation for patients at risk of poor outcomes after knee arthroplasty: CORKA RCT - Barker, KL; Room, J; Knight, R; Dutton, SJ; Toye, F; Leal, J; Kent, S; Kenealy, N; Schussel, MM; Collins, G; Beard, DJ; Price, A; et al. (National Institute for Health Research, 2020)
Background Over 100,000 primary knee arthroplasty operations are undertaken annually in the UK. Around 15–30% of patients do not report a good outcome. Better rehabilitation strategies may improve patient-reported outcomes. Objectives To compare the outcomes from a traditional outpatient physiotherapy model with those from a home-based rehabilitation programme for people assessed as being at risk of a poor outcome after knee arthroplasty. Design An individually randomised, two-arm controlled trial with a blinded outcome assessment, a parallel health economic evaluation and a nested qualitative study. Setting The trial took place in 14 NHS physiotherapy departments. Participants People identified as being at high risk of a poor outcome after knee arthroplasty. Interventions A multicomponent home-based rehabilitation package delivered by rehabilitation assistants with supervision from qualified therapists compared with usual-care outpatient physiotherapy. Main outcome measures The primary outcome was the Late Life Function and Disability Instrument at 12 months. Secondary outcomes were the Oxford Knee Score (a disease-specific measure of function); Knee injury and Osteoarthritis Outcome Score; Quality of Life subscale; Physical Activity Scale for the Elderly; EuroQol-5 Dimensions, five-level version; and physical function assessed using the Figure-of-8 Walk Test, 30-Second Chair Stand Test and Single Leg Stance. Data on the use of health-care services, time off work and informal care were collected using participant diaries. Results In total, 621 participants were randomised. A total of 309 participants were assigned to the COmmunity based Rehabilitation after Knee Arthroplasty (CORKA) home-based rehabilitation programme, receiving a median of five treatment sessions (interquartile range 4–7 sessions). A total of 312 participants were assigned to usual care, receiving a median of four sessions (interquartile range 2–6 sessions). The primary outcome, Late Life Function and Disability Instrument function total score at 12 months, was collected for 279 participants (89%) in the home-based CORKA group and 287 participants (92%) in the usual-care group. No clinically or statistically significant difference was found between the groups (intention-to-treat adjusted difference 0.49 points, 95% confidence interval –0.89 to 1.88 points; p = 0.48). There were no statistically significant differences between the groups in any of the patient-reported or physical secondary outcome measures at 6 or 12 months post randomisation. The health economic analysis found that the CORKA intervention was cheaper to provide than usual care (£66 less per participant). Total societal costs (combining health-care costs and other costs) were lower for the CORKA intervention than usual care (£316 less per participant). Adopting a societal perspective, CORKA had a 75% probability of being cost-effective at a threshold of £30,000 per quality-adjusted life-year. Adopting the narrower health and social care perspective, CORKA had a 43% probability of being cost-effective at the same threshold. Limitations The interventions were of short duration and were set within current commissioning guidance for UK physiotherapy. Participants and treating therapists could not be blinded. Conclusions This randomised controlled trial found no important differences in outcomes when post-arthroplasty rehabilitation was delivered using a home-based, rehabilitation assistant-delivered rehabilitation package or a traditional outpatient model. However, the health economic evaluation found that when adopting a societal perspective, the CORKA home-based intervention was cost-saving and more effective than, and thus dominant over, usual care, owing to reduced time away from paid employment for this group. Further research could look at identifying the risk of poor outcome and further evaluation of a cost-effective treatment, including the workforce model to deliver it. Trial registration Current Controlled Trials ISRCTN13517704. Funding This project was funded by the National Institute for Health Research (NIHR) Health Technology Assessment programme and will be published in full in Health Technology Assessment; Vol. 24, No. 65. See the NIHR Journals Library website for further project information.